Enhancing Learning Interest in Elements and Compounds Materials through Wordwall Interactive Media - Siallagan, Geovani; Rinto; Hidayat, Rahmat; Sihombing, Rizky Agassy (Indonesian Journal of Science and Education, 2025)
This study aims to increase students' interest in learning by implementing Wordwall learning media on the material of elements and compounds. The type of research used is Classroom Action Research which is carried out in two cycles. The subjects of the study were 30 students of class VIII at SMP Negeri 1 Tengahtani. This study used a data collection instrument in the form of a learning interest questionnaire consisting of 7 statements and an observation sheet. In this study, an increase in the average observation score of cycle 1 was obtained by 53.3% with a moderate category to 80% with a high category in cycle 2. Then the questionnaire score also increased, from 63.1% cycle 1 with a high category to 87.25% in cycle 2 with a very high category. This shows an increase in students' interest in learning. Thus, Wordwall media is worthy of being used as an alternative interactive learning strategy to increase students' interest in learning in class.